HIV-1 integrase genotyping is reliable and reproducible for routine clinical detection of integrase resistance mutations even in patients with low-level viraemia. (23rd February 2015) - Armenia, D.; Fabeni, L.; Alteri, C.; Di Pinto, D.; Di Carlo, D.; Bertoli, A.; Gori, C.; Carta, S.; Fedele, V.; Forbici, F.; D'Arrigo, R.; Svicher, V.; et al.
Abstract: Objectives: Integrase drug resistance monitoring deserves attention because of the increasing number of patients being treated with integrase strand-transfer inhibitors. Therefore, we evaluated the integrase genotyping success rate at low-level viraemia (LLV, 51–1000 copies/mL) and resistance in raltegravir-failing patients. Methods: An integrase genotypic resistance test (GRT) was performed on 1734 HIV-1 samples collected during 2006–13. Genotyping success rate was determined according to the following viraemia levels: 51–500, 501–1000, 1001–10 000, 10 001–100 000 and >100 000 copies/mL. The reproducibility of integrase GRT was evaluated in 41 plasma samples processed in duplicate in two reference centres. The relationship between LLV and resistance prevalence was evaluated in a subset of 120 raltegravir-failing patients. Results: Overall, the integrase genotyping success rate was 95.7%. For viraemia levels 51–500 and 501–1000 copies/mL, the rate of success was 82.1% and 94.0%, respectively. GRT was reproducible, producing sequences with a high similarity and an equal resistance profile regardless of the sequencing centre or viraemia level. Resistance was detected both at LLV and at viraemia >1000 copies/mL (51–500 copies/mL = 18.2%; 501–1000 = 37.5%; 1001–10 000 = 53.7%; 10 001–100 000 = 30.0%; and >100 000 = 30.8%). At viraemia ≤500 copies/mL, Q148H/K/R and N155H had the same prevalence (9.1%), while the Y143C/H/R was completely absent. At early genotyping (within 3 months of raltegravir treatment), Q148H/K/R and N155H mutations were detected regardless of the viraemia level, while Y143C/H/R was observed only in samples with viraemia >1000 copies/mL. Conclusions: Our findings prove the reliability of HIV-1 integrase genotyping and reinforce the concept that this assay may be useful in the management of failures even at LLV.